2006
DOI: 10.1007/s11252-006-7902-4
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a micro-bat community in relation to gradients of environmental variation in a tropical urban area

Abstract: We investigated patterns of community structure (species composition, foraging activity, and nightly foraging patterns) of bats in relation to gradients of environmental variation in a tropical urban area. A total of 32 sites spread equally across eight habitat types were sampled in the city of Townsville, North Queensland, Australia. Each site was sampled on 3 non-consecutive occasions using automated AnaBat systems. Eleven species were confidently identified while a possible four more were identified only to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
3
39
0
5
Order By: Relevance
“…While some studies have found a reduction in bat species richness in urban areas compared to surrounding rural areas (Avila-Flores and Fenton 2005), others have found that bat species richness is not affected by urbanization (Kurta and Teramino 1992;Sparks et al 1998;Ulrey et al 2005). However, within cities, bat species richness often declines with the amount of urbanization (Gaisler et al 1998;Hourigan et al 2006). Thus, parks within urban areas may serve as important refuges for bats and may explain why species richness was preserved in the urban parks we studied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While some studies have found a reduction in bat species richness in urban areas compared to surrounding rural areas (Avila-Flores and Fenton 2005), others have found that bat species richness is not affected by urbanization (Kurta and Teramino 1992;Sparks et al 1998;Ulrey et al 2005). However, within cities, bat species richness often declines with the amount of urbanization (Gaisler et al 1998;Hourigan et al 2006). Thus, parks within urban areas may serve as important refuges for bats and may explain why species richness was preserved in the urban parks we studied.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have examined the use of urban areas by bats and have found that bats prefer wooded or riparian areas within cities and avoid high density residential and commercial-industrial areas (Gaisler et al 1998;Gehrt and Chelsvig 2003;Duchamp et al 2004;Sparks et al 2005;Hourigan et al 2006;Walters et al 2007). However, only a few studies have examined the effects of urbanization on bat populations or community composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, some species of bats have been shown to resist anthropogenic effects and sometimes even benefit from them, either by inhabiting urban forest fragments or settling directly in urbanized areas (Bredt and Uieda 1996;Fenton 1997;Esber谩rd 2003;Reis et al 2003;Barros et al 2006). Considering that a better understanding of the influence of urban areas in communities of tropical bats is required (Hourigan 2006), we present here a list of bat species recorded in forest fragments in the municipality of Maring谩, state of Paran谩, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Insectivorous bats (Microchiroptera) are among the native mammalian taxa that persist in Australia's urban environments, but only a small number of studies has examined the ecology of Australia's urban bat populations (Kirsten and Klomp 1998;Hourigan et al 2006;. Little is known about what bat species occur in cities, what food resources are available, and whether populations are viable given the decline of urban insectivorous bat populations overseas (noted by Kurta and Teramino 1992;Arlettaz et al 2000;Guest et al 2002;Duchamp et al 2004).…”
Section: Introductionmentioning
confidence: 99%